Stem Anatomical Descriptors of Four Sesbania Scop. Species And Their Systematic Implication - Chanda, Sontosh C; Mia, Md Ashik; Sagar, Ashaduzzaman; Golam Sarwar, AKM (Bangladesh Journal of Plant Taxonomy, 2021)
Stem anatomical features of four Sesbania Scop. species viz. S. bispinosa (Jacq.) W. Wight, S. cannabina (Retz.) Poir., S. sesban (L.) Merr., and S. rostrata Bremek. & Oberm., were examined to add some insights for identification of these species using quantitative anatomical descriptors. Sesbania stem is composed of epidermis, cortex, vascular tissues – phloem, cambium zone and xylem, and pith, which exhibit significant variations among the species in terms of their area and thickness. Sesbania sesban showed the largest area and widest epidermal cells. The close relationship between S. bispinosa and S. rostrata was found in the stem anatomical descriptors. Moreover, S. rostrata and S. cannabina were closer to some extent according to some anatomical descriptors; also rationalizing the external morphological similarities of these species. A dichotomous key of the studied Sesbania species was made. Dendrograms based on Agglomerative Hierarchical Cluster analysis of stem anatomical descriptors also confirmed close relationships identified in previous phylogenetic analyses. Bangladesh J. Plant Taxon. 28(2): 441-449, 2021 (December)